Ar-turmerone suppresses Aspergillus flavus growth and aflatoxin accumulation: Finding a new antifungal agent based on stored maize. (June 2023) - Li, Zheyu; Sun, Yanan; Gu, Linghui; Wang, Yuchi; Xu, Mingqin; Zhou, Yunhao; Hu, Yichen; Ma, Wenbo
Graphical abstract: Aspergillus flavus is a common saprophytic pathogenic fungus that produces toxic and carcinogenic aflatoxins prone to contaminate food. Here, we synthesised Ar -turmerone, the main active ingredient in turmeric essential oil, optimised the synthesis method to improve yield and reduce operational requirements. Investigated the effects of Ar -turmerone on colony growth, spore germination, mycelium biomass and aflatoxin accumulation. Analysed differentially expressed genes (DEGs) associated with Aspergillus flavus growth and aflatoxin product formation, approximately 2018 DEGs were significantly down-regulated and 34 DEGs were analysed in detail. In addition, the optimal storage conditions for Ar -turmerone to reduce aflatoxin contamination in maize were 0.940 aw, 400.0 μg/mL Ar-turmerone and 16.0 °C. After three weeks of storage under optimal conditions, the maize showed satisfactory evaluation. Highlights: 50.0 μg/mL Ar -turmerone 100.0 % inhibited Aspergillus flavus(A. flavus) and aflatoxin B1 . 2, 018 genes related to A. flavus and aflatoxin were downregulated by Ar -turmerone. Obtained the optimum maize storage condition under Ar- turmerone against A. flavus. Ar- turmerone: a promising candidate for antifungal and anti-aflatoxin inhibitor. Abstract: Aspergillus flavus (A. flavus) is a common saprophytic pathogenic fungus that produces toxic and carcinogenic aflatoxins prone to contaminate food. Here, we optimized the synthesis method of Ar -turmerone, the main active ingredient in turmeric essential oil, improved its yield and reduced the operation requirements. Moreover, 50.0 μg/mL Ar -turmerone 100.0 % inhibited the colonies growth, spore germination, mycelium biomass and aflatoxin accumulation in 7 days. 2, 018 differentially expressed genes (DEGs) such as catA, ppoC, erg7, erg6 and aflO related to the A. flavus growth and aflatoxin product were significantly downregulated including 45 DEGs were 100.0 % suppressed. Besides, Ar -turmerone greatly reduced A. flavus in maize, the optimal storage conditions for maize to avoid A. flavus contamination were determined as 0.940 aw, 400.0 μg/mL Ar -turmerone, and 16.0 °C. Satisfactory odor, luster, taste, and mildew in maize observed after three weeks of storage under the optimal conditions. Thus, Ar -turmerone can be used as a potential food antifungal agent against A. flavus growth and aflatoxin accumulation during food storage.